2014
DOI: 10.1038/ncomms5428
|View full text |Cite
|
Sign up to set email alerts
|

Filamin acts as a key regulator in epithelial defence against transformed cells

Abstract: Recent studies have shown that certain types of transformed cells are extruded from an epithelial monolayer. However, it is not known whether and how neighbouring normal cells play an active role in this process. In this study, we demonstrate that filamin A and vimentin accumulate in normal cells specifically at the interface with Src-or RasV12-transformed cells. Knockdown of filamin A or vimentin in normal cells profoundly suppresses apical extrusion of the neighbouring transformed cells. In addition, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
207
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(228 citation statements)
references
References 40 publications
(70 reference statements)
12
207
4
1
Order By: Relevance
“…Fifth, EPLIN in RasV12-transformed cells substantially affects the accumulation of filamin in the neighboring normal cells and vice versa. In previous studies, we have shown that myosin-II is activated in transformed cells that are surrounded by normal cells and that enhanced myosin-II activity leads to increased cellular elasticity in the transformed cells, which induces the accumulation of the mechanosensor filamin in the neighboring normal cells (Hogan et al, 2009;Kajita et al, 2014). Collectively, our data suggest that EPLIN functions upstream of myosin-II in this process, thereby promoting apical extrusion through filamin.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Fifth, EPLIN in RasV12-transformed cells substantially affects the accumulation of filamin in the neighboring normal cells and vice versa. In previous studies, we have shown that myosin-II is activated in transformed cells that are surrounded by normal cells and that enhanced myosin-II activity leads to increased cellular elasticity in the transformed cells, which induces the accumulation of the mechanosensor filamin in the neighboring normal cells (Hogan et al, 2009;Kajita et al, 2014). Collectively, our data suggest that EPLIN functions upstream of myosin-II in this process, thereby promoting apical extrusion through filamin.…”
Section: Discussionsupporting
confidence: 60%
“…However, the initial step of this process is not clearly understood and remains a 'black box' in cancer biology; when the first mutation occurs in a single cell within epithelia, what happens next? Recent studies have revealed that Ras-, Src-or ErbB2-transformed cells are apically extruded from a monolayer of normal epithelial cells (Grieve and Rabouille, 2014;Hogan et al, 2009;Kajita et al, 2010;Leung and Brugge, 2012;Wu et al, 2014) and that perturbation of proper epithelial organization suppresses this anti-oncogenic process (Hogan et al, 2009;Kajita et al, 2014). During the process of apical extrusion, various signaling pathways are activated in both normal and transformed cells in a non-cell-autonomous fashion.…”
Section: Introductionmentioning
confidence: 99%
“…This localized contraction enables apical constriction during invagination [73] or defines the topography of cell extrusion (apical or basal side of the epithelial monolayer). At the molecular level, cell extrusion directionality is driven by specific oncogenes (Ras, APC) [74,75] and the engagement of N-WASP or crosslinking proteins such as filamins or EPLIN [45,76,77].…”
Section: Thin Bundles and The Regulation Of Lateral Height And Junctimentioning
confidence: 99%
“…In previous studies, we and other groups have demonstrated that when cells with an oncogenic mutation, such as RasV12 or v-Src, are surrounded by normal epithelial cells, the transformed cells are apically extruded from the epithelial monolayer (1)(2)(3)(4)(5). During this process, normal epithelial cells can recognize and actively eliminate the neighboring transformed cells through dynamic regulation of the cytoskeletal protein filamin, a phenomenon called EDAC (epithelial defense against cancer) (6), implying a notion that the normal epithelium has antitumor activity that does not involve immune systems. In addition, EPLIN (epithelial protein lost in neoplasm) is accumulated in transformed cells when they are surrounded by normal epithelial cells, and the EPLIN accumulation plays a crucial role in apical extrusion of the transformed cells (7).…”
mentioning
confidence: 99%